Measuring Performance Efficiency of Application applying Design Patterns and Refactoring Method - Kholed Langsari; Siti Rochimah; Rizky Januar Akbar (IPTEK Journal of Proceedings Series, 2018)
Design patterns are always useful concept using in designing and developing a software application. Performance play essential role in the quality attribute of an enterprise application. It is useful to measure and examine how design patterns influence and affect the performance of an application. In this study, we investigate the impact of selected design pattern through refactoring processes for performance efficiency. The systematic study phases included; analyzing, refactoring and performance measuring with implemented in case study SIA system. The performance measuring measure with different test cases and round for the results comparison of each differences test cases and round for design pattern indicate an influence on the performance of an application